SCENARIO ANALYSIS OF WHOLESALE AND RETAIL TRADE IN BANGLADESH: AN EMPIRICAL EVIDENCE - Neger, Meher (International Journal of Research -GRANTHAALAYAH, 2024)
Wholesale and retail trade is considered as one of the essential activities contributing to the domestic product, labour force and linkage between producers and consumers. The main objective of the study is to assess the status of input cost, gross output, gross value added of wholesale and retail trade in Bangladesh during the period of COVID-19 pandemic and also compare the volatility between wholesale and retail trade. The secondary data of wholesale and retail trade survey-2021 with 15,258 establishment have been collected from Bangladesh Bureau of Statistics (BBS). Both the quantitative and qualitative methods were applied in this study. Scenario analysis was employed to find the current status of input cost, gross output, gross value added of wholesale and retail trade in Bangladesh. The study reveals that industrial cost was increased due to several constraints, including market issues, high labour costs, transportation issues, and logistical shortcomings. The findings of the volatility between wholesale and retail trade represent that retail businesses have more flexibility in expenses, while wholesale enterprises often have more output and value added. Finally, it has been found that gross output significantly depends on gross value addition, whereas COVID-19 affects all scenarios. The findings of this study would be helpful for the planners and policy makers of the trade sectors to take appropriate policies regarding wholesale and retail trade in Bangladesh.